Analysis of Professionalism and The Rights of Film Workers in The Certification Program According to Law Number 33 of 2009 Concerning Film - Natalia, Kartika (Riviera Publishing, 2022)
Introduction: This research aims to invite film workers to take certification rights in government programs in regulating the Indonesian National Work Competency Standards (SKKNI) program and also voice the rights of film workers based on Law Number 13 of 2003 and also Law Number 33 of 2009, with this competency standard, the competitive value of film workers will increase. Moreover, until now, we have experienced that there has yet to be full awareness and massive communication from film workers and business actors. Method: The type of research used is normative-empirical legal research with sociological research methods using secondary data research and interviews. The data analysis used is descriptive qualitative, which contains regular, logical, and effective sentences in the research. Result: So far, the contents of work contracts are often considered to be detrimental to film workers because they do not guarantee normative rights. The government also still places the interests of film workers at the bottom of the list of its work priorities. This is evident in the programs implemented by the three ministries, which tend to answer film entrepreneurs' needs rather than protect workers' interests. Conclusion: The implementation of Law Number 13 of 2003, which regulates employment in general, has yet to be carried out as it should, including for film workers, which is also contained in Law Number 33 of 2009.